Lunat: Tato Tradisional Masyarakat Dawan di Timor Barat - Fransisco de Ch. Anugerah Jacob (Universitas Negeri Medan, 2021)
This article aims to find out the meaning and function of the lunat (traditional tattoo) and the factors causing its absence among the Dawan community in West Timor. According to the Dawanese, lunat has a religious meaning and function, namely as a medium or an instrument of Salvation after someone dies. From the research, four things were found to be the causes why this practice is no longer practiced by the Dawanese nowadays. First is the stigma of being a member or part of the Indonesian Communist Party (PKI). Second is the prohibition of attending school. Third is the disappearance of the lunat religious meaning caused by the transition from traditional religion to Christianity and the fourth is the break in the transfer of knowledge about lunat from one generation to another.